2023
DOI: 10.3390/s23104790
|View full text |Cite
|
Sign up to set email alerts
|

Research on Signal Feature Extraction of Natural Gas Pipeline Ball Valve Based on the NWTD-WP Algorithm

Abstract: The measured signals of internal leakage detection of the large-diameter pipeline ball valve in natural gas pipeline systems usually contain background noise, which will affect the accuracy of internal leakage detection and sound localization of internal leakage points due to the interference of noise. Aiming at this problem, this paper proposes an NWTD-WP feature extraction algorithm by combining the wavelet packet (WP) algorithm and the improved two-parameter threshold quantization function. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As can be seen from figure 9, the predicted values of the Stacking ensemble model are closer to the true values and the prediction is better than each single model. Long-term gas transmission work, unstandardized operation, natural disasters and so on will lead to natural gas pipeline trunk line leakage or explosion and other dangerous situations, the need to perform fire operation on the pipeline When the ball valve leakage in the form of unilateral leakage, the ball valve can still play the role of truncation, can be avoided to empty the ignition point of the natural gas between the two adjacent pipeline segments, reduce economic losses [51]. Therefore, accurate detection of unilateral and bilateral internal leakage of ball valves is very important.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from figure 9, the predicted values of the Stacking ensemble model are closer to the true values and the prediction is better than each single model. Long-term gas transmission work, unstandardized operation, natural disasters and so on will lead to natural gas pipeline trunk line leakage or explosion and other dangerous situations, the need to perform fire operation on the pipeline When the ball valve leakage in the form of unilateral leakage, the ball valve can still play the role of truncation, can be avoided to empty the ignition point of the natural gas between the two adjacent pipeline segments, reduce economic losses [51]. Therefore, accurate detection of unilateral and bilateral internal leakage of ball valves is very important.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…The internal leakage of ball valves is usually determined by regular shutdown and disassembly inspection, which may bring secondary damage [50]. Therefore, research on accurate and efficient nondestructive detection methods for internal leakage is needed [51].…”
Section: Internal Leakage Rate Prediction Model 411 Stacking Ensemble...mentioning
confidence: 99%
“…Selection of threshold: It can be understood from the characteristics of the noise distribution that under the first decomposition scale, the wavelet decomposition coefficients have the highest noise content, which rapidly decays as the wavelet threshold decomposition levels increase. Considering the correction of noise variance on the threshold size, the fixed threshold is adjusted according to the formula as shown in Equation (18). Finally, the calculation formula for the fixed threshold is shown in Equation (19).…”
Section: Selection Of Denoising Model Basic Parametersmentioning
confidence: 99%
“…The simulation results indicated that the proposed method has good denoising effects. Yang et al [ 18 ] presented a denoising model that combines a dual-parameter threshold quantization function with wavelet packet algorithms. The experimental validation demonstrated the feasibility and superiority of this method for denoising pipeline valve leakage signals.…”
Section: Introductionmentioning
confidence: 99%